2017
DOI: 10.3892/mmr.2017.7986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shield1 on the viral replication of varicella‑zoster virus containing FKBP‑tagged ORF4 and 48

Abstract: The present study aimed to explore the effects of a stabilizing ligand, Shield-1, on the replication of recombinant varicella-zoster virus (VZV) containing FK506 binding protein (FKPB) tags in essential open reading frames (ORF) 4 and 48. A specific galactokinase (galK) selection method was conducted, following the addition of galK labels to VZV ORF4 and 48, using a SW102 VZV bacterial artificial chromosome (BAC) system. Subsequently, recombinant VZV containing FKPB tags in ORF4 and 48 was constructed by count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this study, we observed that certain VZV circRNAs are derived from essential genes, such as circRNA 3262 | 4061 and 3699 | 4061, which originates from ORF4. ORF4 is known to be essential for both VZV replication 54 and latency 55 (Fig. 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that certain VZV circRNAs are derived from essential genes, such as circRNA 3262 | 4061 and 3699 | 4061, which originates from ORF4. ORF4 is known to be essential for both VZV replication 54 and latency 55 (Fig. 3A ).…”
Section: Discussionmentioning
confidence: 99%